1973
DOI: 10.1111/j.1365-2818.1973.tb03837.x
|View full text |Cite
|
Sign up to set email alerts
|

High resolution dark‐field electron microscopy

Abstract: Switzerland S U M M A R YIn the last few years some promising images of biological specimens have been obtained using the high contrast and resolution of dark-field electron microscopy. However, important problems of image interpretation and difficulties in specimen preparation limit at the present time, the usefulness of this mode of image formation. The destruction of the sample by the electron beam, is of utmost importance. Some possibilities of partly overcoming it are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1974
1974
1998
1998

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…While standard plastic supports (-300 A) already approgch or exceed this figure, drop films ( -60 A ) leave a considerable margin for specimen dimensions before the resolution limiting thickness is reached. Dark-field electron microscopy has advantages in high resolution since contrast is improved and phase effects are eliminated (Dubochet, 1975). However, this imaging mode is especially sensitive to mass thickness.…”
Section: Volume Of Drop X Concentration Of Solution = Mass Of Formvarmentioning
confidence: 99%
“…While standard plastic supports (-300 A) already approgch or exceed this figure, drop films ( -60 A ) leave a considerable margin for specimen dimensions before the resolution limiting thickness is reached. Dark-field electron microscopy has advantages in high resolution since contrast is improved and phase effects are eliminated (Dubochet, 1975). However, this imaging mode is especially sensitive to mass thickness.…”
Section: Volume Of Drop X Concentration Of Solution = Mass Of Formvarmentioning
confidence: 99%
“…Lattice distortions were recognized by examination of the micrographs or their optical diffraction patterns. Measurements of cell dimensions on 29 specimens all recorded at x 45,000, which were judged to be ] Others have shown that a weak beam somehow stabilizes specimens (1,7,17). Nevertheless, the stain distribution is still sensitive to the effects of further irradiation (3).…”
Section: Hexagonal Lattice Symmetrymentioning
confidence: 99%
“…Small structures might have been lost due to masking effects of the heavy metal. The section might have collapsed during drying although a surrounding contrasting medium is generally supposed to act as a sustaining medium (Dubochet, 1973). Further, effects such as compression during sectioning and shrinkage during drying might have influenced the appearance of the structures in the section.…”
Section: Discussionmentioning
confidence: 99%